COMPUTER TARGET AND STRATEGY FORMATION OF THE INFORMATION SYSTEM SAFETY VIOLATOR - Olga V. Lukinova (Открытое образование (Москва))
The article deals with communication of strategic, tactical targets and the strategy realized by the violator of safety of information system. Semantic models and algorithms are developed for a conclusion of the purposes and strategies; criteria and tasks for strategies assessment, based on representation of information system in the form of the open environment model are described.